ANALISIS EFEKTIVITAS PENGENDALIAN INTERN DALAM PENERIMAAN RETRIBUSI PASAR PADA DINAS KOPERASI, UMKM, DAN PENGELOLAAN PASAR DI KECAMATAN SEKAYU KABUPATEN MUSI BANYUASIN - Asoka, Rano (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to determine how the effectiveness of internal control in receiving market fees on the Cooperative Office, UMKM, and Market Management in Sekayu District, Musi Banyuasin Regency. Data collection techniques carried out through interviews (interviews) Observation, Documentation and Literature Study. Data analysis uses quantitative analysis. The results of the analysis show that the internal control system applied at the Department of Cooperatives, UMKM, and Market Management in Sekayu District, Musi Banyuasin Regency has been effective, but the collection of fees has not reached the desired target because there are still obstacles and fraud from the collection of the market levies themselves.Targeting as a condition in the collection of market levies has been done monthly by the Office of Cooperatives, UMKM, and Market Management in Sekayu District, Musi Banyuasin Regency. In the implementation of market levies to traders there are some obstacles that have still not been resolved, even though the existence of these obstacles will have an impact on reducing the acceptance of market charges. In the market levies or levies carried out by the Department of Cooperatives, MSMEs, and Market Management in Sekayu District, Musi Banyuasin District the results are quite good, but in the implementation of the collection there are still weaknesses, namely by still having the dual functions and tasks in the administration section